Odpowiedzi

2010-01-23T18:13:41+01:00
1. = 2: 3/8 * (-2/6)= 3/4 * (-2/6) = 1/2 * (-1/2) = - 1/4
2.= 10*(- 7/20 )*3/7= -7/2 * 3/7 = 1/2 * 3/1 = 3/2
3/ = 10 * 5/2 : (-3/2)= 5/5: (-3/2)= 5/5 * (-2/3)= - 10/15
4. = (- 12 + 21/2): (-1/2)= 15: (-1/2)= 15 *(-2/1) = 30
5. = 13- 82/9 * 6/2 + 13 - 41/3 * 21 = 13- 82/3
6. = -10/3 : ( 22.3 + 8/3 + 1) = - 10/3: (30/3+1) =
jak gdzieś zrobiłam błąd to sorry.
2010-01-23T18:43:10+01:00
(4:8/6)x(-2/6)= 3*(-2/6) = -1
(10:(-20/7))x3/7= -7/2*3/7 = -1,5
(10x-2 ½):(-3/2)= -25:(-3/2) = 16²/₃
(-12+10½);(-1/2)= -1¹/₂:(-1/2) = 3
(13-9 1/9);2/6= 3⁸/₉:2/6 = 11⁶/₉
-3⅓;(7⅓+2⅔+1)= -3⅓:11 = -10/33